Designing and Evaluation of a Plasmid Encoding Immunogenic Epitopes From Echinococcus granulosus Eg95-1-6, P29, and GST Against Hydatid Cyst in BALB/c Mice - Sasan Khazaei; Abdolhossein Dalimi; Majid Pirestani; Fatemeh Ghafarifar (Journal of Parasitology Research)
Cystic echinococcosis (CE) is a neglected parasitic infection with a particular impact in humans and livestock. The current investigation was undertaken to design and evaluate a DNA vaccine encoding Echinococcus granulosus Eg95-1 to EG95-6, P29, and GST against hydatid cyst infection in BALB/c mice. Initially, B-cell, cytotoxic T-lymphocyte, and helper T-lymphocyte epitopes were forecasted using B-cell epitope prediction server (BCPREDS) and Immune Epitope Database (IEDB) server, respectively, and a vaccine construct incorporating multiple epitopes was rationally designed and comprehensively analyzed through in silico modeling and simulation studies. Next, Escherichia coli TOP10 was transformed by the recombinant pcDNA 3.1 plasmid and mass production, followed by plasmid extraction, was done. The BALB/c mouse immunization was done with 50 and 100 μg concentrations of plasmid combined with IL-12 adjuvant or alone. Mouse sera and splenic lymphocytes were used for the measurement of specific humoral and cellular responses. The candidate vaccine model weighed 37.49 kDa with 338 residues antigenic, while nonallergenic, soluble, stable, highly thermotolerant, and hydrophilic in nature. Expression in HEK-293 cells was successfully achieved, as evidenced by the detection of a 37 kDa protein band in the western blot analysis. Vaccine doses, especially the 100 μg concentration, alone or in combination with an adjuvant, induced a T-helper 1 (Th1)–type immune response. This was evidenced by higher levels of IgG2a antibody and interferon gamma (IFN-γ) along with lower levels of interleukin 4 (IL-4). Although the groups that received the 50-μg dose of vaccine alone or with adjuvant showed a lower immune response, overall, the vaccinated groups showed statistically significant differences compared to the control groups (phosphate-buffered saline (PBS) and pcDNA). The promising results of this vaccine candidate can be further examined using challenges with various parasite genotypes.